(untitled) (Bangladesh Medical Journal, 2026)
Dyspepsia is a common upper gastrointestinal symptom complex with overlapping functional and organic etiologies. Among Helicobacter pylori (H. pylori)-positive patients, symptom patterns frequently demonstrate poor correlation with endoscopic findings. This study evaluated the clinico‑endoscopic distribution of dyspepsia subtypes and their associated predictors among H. pylori–positive adults without alarm features. This cross‑sectional study analyzed baseline data from a randomized controlled trial conducted among treatment‑naïve adults aged ≥18 years with H. pylori-positive dyspepsia. Dyspepsia was categorized according to Rome IV criteria into Epigastric Pain Syndrome (EPS), Postprandial Distress Syndrome (PDS), and mixed subtype. Upper gastrointestinal endoscopy classified patients as functional dyspepsia (FD) or organic dyspepsia (OD). Descriptive statistics, chi‑square test, Student’s t‑test, ANOVA, and multinomial logistic regression were performed. Odds ratios (OR) with 95% confidence intervals (CI) were reported, and p<0.05 was considered statistically significant. A total of 80 participants were included, with a mean age of 35.8±11.4 years; 53.7% were female, and 52.5% resided in rural areas. Mixed dyspepsia was the most frequent subtype (55.0%), followed by EPS (28.8%) and PDS (16.3%). Functional dyspepsia accounted for 51.2% of cases, whereas organic dyspepsia was observed in 48.8%. Abnormal endoscopic findings were significantly more frequent among EPS and PDS subtypes (p<0.001). Erosive gastritis was the most common abnormality (23.8%), followed by non‑erosive gastritis (15.0%). Epigastric pain, epigastric burning, postprandial fullness, and early satiety were significantly more common in FD than OD (all p<0.01). Organic dyspepsia was significantly associated with age ≥34 years (OR 1.90; p=0.008) and smoking history (OR 1.76; p=0.019). Multinomial logistic regression demonstrated that symptom duration ≥12 months (OR 9.04; p=0.005) and normal endoscopy/FD (OR 17.00; p<0.001) independently predicted mixed dyspepsia. Mixed dyspepsia was the predominant symptom phenotype among H. pylori-positive adults. Functional dyspepsia was strongly associated with overlapping symptom patterns, whereas EPS and PDS were more frequently associated with organic abnormalities. Symptom duration and endoscopic status were stronger predictors of dyspepsia subtype than demographic variables, supporting an integrated clinico‑endoscopic approach for evaluation and stratification. Bangladesh Med J. 2025 Sept; 54(3): 24-31